Malrotation of Gut: Presentation in Adults - A Case Series - K N Rajesh; H R Pallavi; Suprabha R Hegde; Akshata M Goudar (Journal of Medical Sciences and Health)
Intestinal malrotation is arrested normal rotation of the gut during development. Malrotation seldom presents in adults and often not timely diagnosed. These diagnostically challenging cases may lead to worser outcomes, with increase in morbidity and motility compared to paediatric age group. 1 We present six such rare diagnostically challenging cases of adult presentation of malrotation of gut. Five rare presentations of malrotation of gut during a period of three years (2020- 2023). Outcome was analysed retrospectively. Among the five patients, four were male and one was female. Youngest patient was 18 years and the oldest in the study was an 80-year-old male. All patients presented with multiple episodes of bilious vomiting and vague symptoms of pain abdomen. All five had varying degree of malrotation of gut. Patients underwent Erect Xray abdomen, and contrast-enhanced computed tomography abdomen and diagnostic laparotomy to confirm the diagnosis. All five patients underwent Ladd procedure or division of peritoneal bands with one requiring right hemicolectomy with end ileostomy. Four had favourable outcomes post procedure whereas one underwent reversal of end ileostomy procedure two months post hemicolectomy.